2007
DOI: 10.1002/nme.2020
|View full text |Cite
|
Sign up to set email alerts
|

Embedded strong discontinuity finite elements for fractured geomaterials with variable friction

Abstract: SUMMARYThe strong discontinuity approach to modelling strain localization, combined with an enhanced strain element, has been used for more than a decade to model strain localization in materials including geomaterials. Most implementations of enhanced strain elements in the post-localization regime use very simple constitutive formulations along the discontinuity, such as linear softening or a constant friction coefficient. However, the softening relations can be much more complex for geomaterials. For rocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 61 publications
2
53
0
Order By: Relevance
“…This equation predicts a nonlinear slip weakening similar to Figure 3(b) for the case of a variable t N (concave downwards or upwards depending on whether t N decreases or increases during slip weakening), and recovers a linear slip weakening for the case of a constant t N , see [21,34] for further details.…”
Section: Slip Weakeningsupporting
confidence: 58%
See 3 more Smart Citations
“…This equation predicts a nonlinear slip weakening similar to Figure 3(b) for the case of a variable t N (concave downwards or upwards depending on whether t N decreases or increases during slip weakening), and recovers a linear slip weakening for the case of a constant t N , see [21,34] for further details.…”
Section: Slip Weakeningsupporting
confidence: 58%
“…The upper block was sheared relative to the lower block, mimicking the experiment for granite with a #60 surface subjected to a 15 MPa normal stress [33]. The same experimental curve was earlier reproduced by Foster et al [21] using the assumed enhanced strain FE formulation; here we used the same parameters along with the extended FE simulation. The slip speed began at V 1 = 10 −5 m/s for 2 s, increased to V 2 = 10 −4 m/s for 2 s, and finally decreased back to V 3 = 10 −5 m/s for 2 s. Time increment used in the simulation is t = 0.002 s and the total relative displacement is 0.24 mm after 6 s. The material properties used in the simulation are listed in Table I.…”
Section: Sliding Of a Pre-fractured Granite Blockmentioning
confidence: 99%
See 2 more Smart Citations
“…The EFEM has been applied to many interesting problems [103][104][105][106] including piezoelectric materials [107], geomaterials [108], coupled formulations [109], finite strains [110], crack branching [111], and dynamic fracture [112], to name a few. Oliver et al [113] compared embedded elements with the extended finite element method (that will be discussed in the next section) (XFEM) for several selected examples and showed that embedded elements can be as accurate as XFEM.…”
Section: Embedded Elements (Efem)mentioning
confidence: 99%